Scordatura na performance: o uso da scordatura na versão para viola na Suíte n. 5 de J. S. Bach - Maria Fernanda Leitão Canabarro (2013)
This work aims to study the use of scordatura for viola, focusing on the Suite for Violoncello Solo n. 5 of J. S. Bach. This technique was dropped over time by apparently presenting greater difficulty in performance than when using the standard tunning of the viola. However, scordatura reveals to be a positive practice when performing Bach's Suite no. 5. The use of this technique shows technical and interpretive displays qualities such as, fingering and sound, favorable to performance and also makes the execution of the work hold true to the composer's original version.